A Comprehensive Analysis of Narrative and Character Elements in The Conjuring (2013) Through Repertoire of Elements and Propp's Theory - Indradewi, Amalia; Jayantini, I Gusti Agung Sri Rwa (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
This study provides a comprehensive analysis of the 2013’s movie The Conjuring through Nick Lacey’s Repertoire of Elements and Vladimir Propp’s Narrative Theory. The movie, directed by James Wan, is recognized for its intricate horror narrative and rich character development. By examining the movie’s use of style, iconography, character roles, narrative structure, and setting, this research demonstrated how these elements worked together to create a compelling supernatural experience. Applying Lacey’s theory revealed the movie’s adherence to genre conventions through its dark, atmospheric settings and minimal lighting. Interestingly, the movie did not feature a